Transforming Islamic Educational Management in the Artificial Intelligence Era: An Outcome-Based, Human-Centred Evaluation Model for Islamic Religious Education Curriculum - Muhamad Zaini Fajri, Zainul Arifin, Welly Kuswanto (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The transformation of Islamic educational management in the era of artificial intelligence requires a curriculum evaluation framework that is not limited to administrative compliance, final grades, or accreditation-oriented reporting. This article aims to reformulate an Outcome-Based Education evaluation model for the Islamic Religious Education curriculum as a human-centred, ethically governed, and evidence-informed approach to Islamic higher education management. The study employed a sequential explanatory mixed methods design, in which the quantitative phase was directed toward construct development, instrument design, expert validation, factor analysis, reliability estimation, and model implementation analysis, while the qualitative phase deepened the quantitative findings through interviews, observation, document study, and focus group discussion. The most significant finding is the need for an integrated evaluation model that connects graduate profiles, program learning outcomes, course learning outcomes, learning processes, assessment practices, evidence of achievement, stakeholder responses, unintended outcomes, pathways of change, and continuous improvement. The article contributes theoretically by positioning Islamic educational management as a governance practice that must integrate Outcome-Based Education, constructive alignment, responsive evaluation, theory of change, and ethical AI-oriented data use within pesantren-based Islamic higher education